Early development of self‐administered COVID‐19 rapid test based on nucleocapsid detection in saliva sample - Siti Soidah; Toto Subroto; Sari Syahruni; Fauzian Giansyah; Henry Chandra; Dhiya Salsabila; Bachti Alisjahbana; Nisa Fauziah; Hesti Lina Wiraswati; Leonardus Wiydatmoko; Basti Andriyoko; Anita Yuwita; Muhammad Yusuf (Indonesian Journal of Biotechnology, 2022)
More than 6,000,000 people have died due to the coronavirus (COVID‐19) pandemic. This disease spread quickly due to its highly contagious nature. The SARS‐CoV‐2 virus that causes the disease can be transmitted through saliva droplets secreted by infected people at a distance of less than 1 m. As a result, saliva has been accepted as an alternative specimen for COVID‐19 detection by the Centers for Disease Control and Prevention (CDC). Furthermore, WHO recommended the use of rapid antigen tests based on lateral flow immunoassay when reverse transcription‐polymerase chain reaction (RT‐PCR) is not available. We developed a saliva‐based rapid antigen test by optimizing the antibody concentration and optimum pH for the conjugation of antibody and gold nanoparticles. We found that the best running buffer formulation consisted of 75 mM sodium phosphate buffer, 1% NaCl, 1% Triton X‐100, 0.5% N‐acetyl‐L‐cysteine, and 0.02% sodium azide. The addition of a mucolytic agent in the buffer can reduce the viscosity of saliva, thus improving sensitivity. The rapid test developed detected the lowest concentration of nucleocapsid protein at 0.1 μg/mL. Our study revealed 100% specificity against negative COVID‐19 saliva and no cross‐reaction with avian influenza virus hemagglutinin.